A comment on "Nonlinear thermal buckling of axially functionally graded micro and nanobeams" [Composite Structures 168 (2017) 428–439]. (15th October 2017) - Dehrouyeh-Semnani, Amir Mehdi
Abstract: In a recent paper by Shafiei, Mirjavadi, Afshari, Rabby, and Hamouda [1], for the first time the nonlinear mathematical formulations of axially functionally graded (AFG) micro/nano-beams under non-uniform temperature distribution in the thickness direction based on the classical theory as well as the non-classical theories (modified couple stress and nonlocal theories) were developed to study the thermal buckling of system. In this comment, it is indicated that the governing equations and associated boundary conditions of system were incompletely established not only for the non-classical models but also for the classical model. The main reason for the inaccuracy of mathematical formulations proposed by Shafiei et al. [1] is to neglect the influence of thermal moment at both the governing equations and boundary conditions. In addition, it is discussed that the size-dependent and -independent buckling temperature rise predicted by Shafiei et al. [1] is meaningless for both the simply supported and fully clamped case studies.